Statistical approximation of multicriteria problems of stochastic programming - Norkin, B.V. (Доповіді НАН України, 2015)
The article validates an approximation technique for solving multiobjective stochastic optimization problems. As a generalized model of a stochastic system to be optimized, a vector “input–random output” system is considered. Random outputs are converted into a vector of
deterministic performance/risk indicators. The problem is to find those inputs that correspond
to Pareto-optimal values of output indicators. The problem is approximated by a sequence
of deterministic multicriteria optimization problems, where, for example, the objective vector
function is a sample average approximation of the original one, and the feasible set is a discrete sample approximation of the feasible inputs. Approximate optimal solutions are defined as weakly Pareto efficient ones within some vector tolerance. Convergence analysis includes
establishing the convergence of the general approximation scheme and establishing the conditions of convergence with probability one under proper regulation of sampling parameters. Обгрунтовано апроксимацiйний пiдхiд до розв’язання задач багатокритерiальної стохастичної оптимiзацiї. В якостi узагальненої моделi стохастичної системи, що оптимiзується, використовується векторна модель типу “вхiд–випадковий вихiд”. Випадковi виходи перетворюються в вектор детермiнованих показникiв ефективностi i ризику. Проблема полягає в тому, щоб знайти тi входи, якi вiдповiдають Парето-оптимальним значенням вихiдних показникiв. Ця задача наближається послiдовнiстю задач детермiнованої багатокритерiальної оптимiзацiї, де, наприклад, цiльова вектор-функцiя є вибiрковим середнiм наближенням вихiдної функцiї, а допустима множина є дискретним наближенням можливих входiв. Наближенi оптимальнi розв’язки визначаються як слабо ефективнi (з деякою точнiстю) за Парето. Аналiз збiжностi включає в себе обгрунтування збiжностi загальної
апроксимацiйної схеми i встановлення умов збiжностi з ймовiрнiстю одиниця при адекватному регулюваннi параметрiв вибiрки. Обосновывается аппроксимационный подход к решению задач многокритериальной стохастической оптимизации. В качестве обобщенной модели оптимизируемой стохастической системы используется векторная модель типа “вход–случайный выход”. Случайные выходы
преобразуются в вектор детерминированных показателей эффективности и риска. Проблема состоит в том, чтобы найти те входы, которые соответствуют Парето-оптимальным значениям выходных показателей. Эта задача приближается последовательностью
задач детерминированной многокритериальной оптимизации, где, например, целевая вектор-функция является выборочным средним приближением исходной функции, а допустимое множество является дискретным приближением возможных входов. Приближенные
оптимальные решения определяются как слабо эффективеные (с некоторой точностью) по
Парето. Анализ сходимости включает в себя обоснование сходимости общей аппроксимационной схемы и установление условий сходимости с вероятностью единица при адекватном регулировании параметров выборки.